Maternal cognitions and mother-infant interaction in postnatal depression and generalized anxiety disorder. - Stein, A; Craske, MG; Lehtonen, A; Harvey, A; Savage-McGlynn, E; Davies, B; Goodwin, J; Murray, L; Cortina-Borja, M; Counsell, N (2012)
Postnatal depression and anxiety have been shown to increase the risk of disturbances in mother-child interaction and child development. Research into mechanisms has focused on genetics and maternal behavior; maternal cognitions have received little attention. Our aim was to experimentally determine if worry and rumination in mothers with generalized anxiety disorder (GAD) and major depressive disorder (MDD), diagnosed in the postnatal 6 months, interfered with maternal responsiveness to their 10-month old infants. Mothers (N = 253: GAD n = 90; MDD n = 57; control n = 106) and their infants were randomized to either a worry/rumination prime (WRP) or a neutral prime (NP); mother-infant interactions were assessed before and after priming. Type of priming was a significant predictor of maternal cognitions, with WRP resulting in more negative thoughts, higher thought recurrence and more self-focus relative to NP across the entire sample. Interaction effects between group and priming were significant for two parenting variables: Compared with controls, WRP had a more negative impact on maternal responsiveness to infant vocalization for GAD, and to a lesser extent for MDD; WRP led to decreased maternal vocalization for GAD. Also, mothers with GAD used stronger control after the NP than WRP, as well as compared with other groups, and overall post-priming, their children exhibited lower emotional tone and more withdrawal. Across the entire sample, WRP was associated with increased child vocalization relative to NP. This study demonstrated that disturbances in maternal cognitions, in the context of postnatal anxiety and to a lesser degree depression, play a significant role in mother-child interaction.